Pembagian Harta Gono Gini Akibat Perceraian WNI dan WNA Inggris Tanpa Berdasarkan Asas Choice Of Law - Rizki Dwi Putra; Illa Fatikha Syahda; Tazkia Suhail Syafa (Sharia Faculty of State Islamic Institute (IAIN) Palangka Raya, 2025)
Marriages involving two different legal systems often give rise to various problems, especially regarding the division of property when divorce occurs. If the couple does not make a marriage agreement before or during the marriage, then the property is considered as joint property. However, property obtained before marriage is considered as the personal property of each spouse. In resolving the division of joint property, several countries have different legal systems. In international civil law, there is the principle of Lex Rei Sitae, which stipulates that the law applicable to an object is determined based on the location of the object. This provides fair legal certainty for the parties in determining the rights to the property. This research uses the normative juridical method, namely by examining, studying, and interpreting the applicable legal rules. This writing aims to analyze the problem of divorce and the legal principles used in the division of gono-gini property. In conclusion, the Lex Rei Sitae principle is considered capable of providing appropriate legal certainty because it considers the location of the object as the basis for determining ownership. Keywords: Abstrak Perkawinan yang melibatkan dua sistem hukum yang berbeda sering kali memunculkan berbagai masalah, terutama terkait pembagian harta kekayaan saat perceraian terjadi. Jika pasangan tidak membuat perjanjian pernikahan sebelum atau saat perkawinan berlangsung, maka harta kekayaan tersebut dianggap sebagai harta bersama. Namun, harta yang diperoleh sebelum pernikahan dianggap sebagai harta pribadi masing-masing pasangan. Dalam penyelesaian pembagian harta gono-gini, beberapa negara memiliki sistem hukum yang berbeda. Dalam hukum perdata internasional, terdapat asas Lex Rei Sitae, yang menetapkan bahwa hukum yang berlaku atas suatu benda ditentukan berdasarkan lokasi benda tersebut. Hal ini memberikan kepastian hukum yang adil bagi para pihak dalam menentukan hak atas harta tersebut. Penelitian ini menggunakan metode yuridis normatif, yaitu dengan mengkaji, mempelajari, dan menafsirkan aturan hukum yang berlaku. Penulisan ini bertujuan untuk menganalisis masalah perceraian dan asas hukum yang digunakan dalam pembagian harta gono-gini. Sebagai kesimpulan, asas Lex Rei Sitae dinilai mampu memberikan kepastian hukum yang tepat karena mempertimbangkan lokasi benda sebagai dasar penentuan kepemilikan. Kata kunci: Perkawinan, Harta, Asas Abstract Marriages involving two different legal systems often give rise to various problems, especially regarding the division of property when divorce occurs. If the couple does not make a marriage agreement before or during the marriage, then the property is considered as joint property. However, property obtained before marriage is considered as the personal property of each spouse. In resolving the division of joint property, several countries have different legal systems. In international civil law, there is the principle of Lex Rei Sitae, which stipulates that the law applicable to an object is determined based on the location of the object. This provides fair legal certainty for the parties in determining the rights to the property. This research uses the normative juridical method, namely by examining, studying, and interpreting the applicable legal rules. This writing aims to analyze the problem of divorce and the legal principles used in the division of gono-gini property. In conclusion, the Lex Rei Sitae principle is considered capable of providing appropriate legal certainty because it considers the location of the object as the basis for determining ownership. Keywords: Abstrak Perkawinan yang melibatkan dua sistem hukum yang berbeda sering kali memunculkan berbagai masalah, terutama terkait pembagian harta kekayaan saat perceraian terjadi. Jika pasangan tidak membuat perjanjian pernikahan sebelum atau saat perkawinan berlangsung, maka harta kekayaan tersebut dianggap sebagai harta bersama. Namun, harta yang diperoleh sebelum pernikahan dianggap sebagai harta pribadi masing-masing pasangan. Dalam penyelesaian pembagian harta gono-gini, beberapa negara memiliki sistem hukum yang berbeda. Dalam hukum perdata internasional, terdapat asas Lex Rei Sitae, yang menetapkan bahwa hukum yang berlaku atas suatu benda ditentukan berdasarkan lokasi benda tersebut. Hal ini memberikan kepastian hukum yang adil bagi para pihak dalam menentukan hak atas harta tersebut. Penelitian ini menggunakan metode yuridis normatif, yaitu dengan mengkaji, mempelajari, dan menafsirkan aturan hukum yang berlaku. Penulisan ini bertujuan untuk menganalisis masalah perceraian dan asas hukum yang digunakan dalam pembagian harta gono-gini. Sebagai kesimpulan, asas Lex Rei Sitae dinilai mampu memberikan kepastian hukum yang tepat karena mempertimbangkan lokasi benda sebagai dasar penentuan kepemilikan. Kata kunci: Perkawinan, Harta, Asas Abstract Marriages involving two different legal systems often give rise to various problems, especially regarding the division of property when divorce occurs. If the couple does not make a marriage agreement before or during the marriage, then the property is considered as joint property. However, property obtained before marriage is considered as the personal property of each spouse. In resolving the division of joint property, several countries have different legal systems. In international civil law, there is the principle of Lex Rei Sitae, which stipulates that the law applicable to an object is determined based on the location of the object. This provides fair legal certainty for the parties in determining the rights to the property. This research uses the normative juridical method, namely by examining, studying, and interpreting the applicable legal rules. This writing aims to analyze the problem of divorce and the legal principles used in the division of gono-gini property. In conclusion, the Lex Rei Sitae principle is considered capable of providing appropriate legal certainty because it considers the location of the object as the basis for determining ownership. Keywords: Marriage, Property, Principal